2017
DOI: 10.1080/00016357.2017.1279345
|View full text |Cite
|
Sign up to set email alerts
|

Dental trauma and bicycle safety: a report in Italian children and adolescents

Abstract: Il presente documento viene fornito attraverso il servizio NILDE dalla Biblioteca fornitrice, nel rispetto della vigente normativa sul Diritto d'Autore (Legge n.633 del 22/4/1941 e successive modifiche e integrazioni) e delle clausole contrattuali in essere con il titolare dei diritti di proprietà intellettuale.La Biblioteca fornitrice garantisce di aver effettuato copia del presente documento assolvendo direttamente ogni e qualsiasi onere correlato alla realizzazione di detta copia. La Biblioteca richiedente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In our study, the number of dental traumas peaked among toddlers (1-2 years old) and 7-to 9-year-old school children. These findings are in line with the results of similar studies, 16,17 though other studies have reported TDI peaks in older school children (8-10 years) [18][19][20] and found no similarly high frequency of TDIs in toddlers. 21 In our study, most TDIs (87.7%) occurred in children under 10 years, while only 13.3% of TDIs occurred in children over 10 years.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the number of dental traumas peaked among toddlers (1-2 years old) and 7-to 9-year-old school children. These findings are in line with the results of similar studies, 16,17 though other studies have reported TDI peaks in older school children (8-10 years) [18][19][20] and found no similarly high frequency of TDIs in toddlers. 21 In our study, most TDIs (87.7%) occurred in children under 10 years, while only 13.3% of TDIs occurred in children over 10 years.…”
Section: Discussionsupporting
confidence: 91%
“…In these cases, both dentists and sports centre staff might suggest the use of helmets, mouthguards and/or facemasks suitable for the sport being practised, informing players of the risk of dental and facial damages and of the benefits of these safety measures [16, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…5 An Italian paper reported that facial and dental injuries related to bicycle accidents included crown fractures, periodontal injuries, maxillo-facial bone fractures as well as soft tissue lacerations and contusions. 6 A relevant finding noted by these authors was that facial fractures more frequently involved the mid-face in younger individuals, whilst the mandible, maxilla and zygoma suffered in slightly older children.…”
mentioning
confidence: 89%
“…The cause was due to the formation of a post-traumatic intramural thrombus in the internal carotid artery (which lies in close proximity to the posterolateral oropharynx), which then resulted in a haemorrhagic stroke possibly due to embolization of the thrombus to the middle cerebral artery in the Circle of Willis. 6 Bicycle riding is accompanied by a high risk of injury. Safety precautions such as helmet usage are of pivotal importance in terms of prevention.…”
Section: < 561mentioning
confidence: 99%